Efficacy and safety of different insulin infusion methods in the treatment of total parenteral nutrition-associated hyperglycemia: a systematic review and network meta-analysis - Cao, Lu; Zhang, Dan; Zhao, Ying; Zhou, Nan; Zhang, Peng (Frontiers in Nutrition, 2023)
Aims: To systematically evaluate the efficacy and safety of different insulin infusion methods in the treatment of total parenteral nutrition (TPN)-associated hyperglycemia based on published literature and the data of completed clinical trials using a network meta-analysis. Methods: A comprehensive search up to December 15, 2022, was performed to collect information on different insulin infusion methods used for the treatment of TPN-associated hyperglycemia, and the Cochrane systematic review method was used to screen the literature, evaluate the quality of the included literature, and extract clinical characteristics for a network meta-analysis. Clinical outcomes included mean blood glucose (MBG), hypoglycemia, hospital length of stay, hyperglycemia, surgical site infection (SSI) and mean total daily insulin. Results: A total of 21 articles, including 1459 patients, were included to analyze 6 different routes of insulin infusion, including continuous intravenous insulin infusion (CVII), continuous subcutaneous insulin infusion (CSII), subcutaneous glargine insulin (s.c. GI), the addition of regular insulin to the PN mixture (RI-in-PN), multiple subcutaneous insulin injections (MSII) and 50% of insulin administered as RI-in-PN + 50% of insulin administered as s.c. GI (50% RI-in-PN + 50% s.c.GI). The results of the network meta-analysis showed that MSII was the least effective in terms of MBG, followed by CVII. The 6 interventions were basically equivalent in terms of the hypoglycemia incidence. In terms of the length of hospital stay, patients in the CVII group had the shortest hospital stay, while the MSII group had the longest. CVII was the best intervention in reducing the incidence of hyperglycemia. The incidence of SSI was the lowest in the CSII and CVII groups, and the mean daily insulin dosage was the lowest in the CVII group. Conclusion: Current literatue shows that for the treatment of TPN-associated hyperglycemia, CVII is the most effective, reducing the incidenceof hyperglycemia and shortening the length of hospital stay without increasing the incidence of hypoglycemia. MSII has the worst efficacy, leading to a higher MBG and longer hospital stay, and RI-in-PN, CSII, s.c.GI and 50% RI-in-PN + 50% s.c.GI are better in terms of efficacy and safety and can be substituted for each other.